Students Perceptions in Choosing the Sharia Banking Major in Relation to Future Career Prospects (Case Study on Sharia Banking Students at UINSU) - Annisa Aulia Azzahra; Tuti Anggraini; Ahmad Perdana Indra (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Student perception plays a vital role in shaping attitudes, interests, and decisions, particularly in choosing a major and planning a career. Each individual has different perceptions depending on background, expectations, and information received. This study aims to explore the perceptions of final-year and new students in choosing the Sharia Banking major with regard to career prospects. Many students still believe that graduates can only work in banks, although opportunities are more diverse. The research method applied is qualitative, using open-ended questionnaires distributed to 100 respondents, consisting of 50 new and 50 final-year students. The findings show that final-year students possess a broader understanding due to academic and internship experiences, while new students tend to have limited views. Factors influencing perceptions include experience, knowledge, and environment. The study suggests the need for early career prospect socialization, stronger collaboration between universities and industry, and students’ active efforts in seeking information and developing skills.